Encountering Adamastor South Africa's founding geographers in time and place - Barnard, W.S (African Sun Media, 2016)
The volume of W.S. Barnard is a first in a series of life-histories of the founding geographers in South Africa published by the Centre of Geographical Analysis at Stellenbosch University. Life-histories are reported in five ways: the commendation lauds the winner of an award; the obituary by necessity speaks well of the dead; the brief entry in a dictionary or encyclopedia is highly stylized and constrained by editorial guidelines; in the autobiography the author tells his own story in his own way; and, finally, the biography comes in a range of formats and structures. At the one extreme is the complete life-history, written by a specialist following the historiographical method and based on the critical assessment of primary sources; at the other is the belletristic overview: descriptive, anecdotal, facile and artful.